Analysis of turbulent flows - Cebeci, Tuncer (Elsevier, 2004)
Modelling and Computation of Turbulent Flows has been written by one of the most prolific authors in the field of CFD. Professor of aerodynamics at SUPAERO and director of DMAE at ONERA, the author calls on both his academic and industrial experience when presenting this work. The field of CFD is strongly represented by the following corporate companies; Boeing; Airbus; Thales; United Technologies and General Electric, government bodies and academic institutions also have a strong interest in this exciting field. Each chapter has also been specifically constructed to constitute as an advanced textbook for PhD candidates working in the field of CFD, making this book essential reading for researchers, practitioners in industry and MSc and MEng students.
Previous ed.: published as Analysis of turbulent boundary layers. New York; London: Academic, 1974.
Keywords: Turbulence.; elektronické knihy; electronic books